A Review on Power Plant Maintenance and Operational Performance - Velayutham P.; Ismail F.B. (EDP Sciences, 2023)
Electric power systems; Particle swarm optimization (PSO); Scheduling; Load demand; Maintenance scheduling; Objective functions; Operational performance; Particle swarm optimization technique; Power plant maintenance; Power System; Reliable operation; Maintenance